PENGARUH EVALUASI ANGGARAN, PSYCHOLOGICAL CAPITAL DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA APARATUR PEMERINTAH DI KOTA LANGSA - Annisa Farhani; Tuti Meutia; Salman, Muhammad (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This study aims to determine the effect of Budget Evaluation, Psychological Capital and Budget Goal Clarity on the Performance of Government Apparatus in Langsa City. The technique uses a saturated sample with a sample size of 105 respondents. The data collection method uses a questionnaire. The data analysis method used in this study is multiple linear regression, t test, F test and determination coefficient test. t test is known that budget evaluation with a tsig value of 0.896> 0.05 has no significant effect, psychological capital with a tsig value of 0.000 <0.05 has a significant effect on the performance of government officials, and budget target clarity with a tsig value of 0.732> 0.05 has no significant effect on the performance of government officials. The results of the F test showed that the Fsig value of 0.000 <0.05 means that budget evaluation, psychological capital and budget target clarity simultaneously have a significant effect on the performance of government officials. The coefficient of determination obtained is 0.243 or 24.3%, while the remaining 0.998 or 99.8% is influenced by other variables.